1999
DOI: 10.1155/mbd.1999.355
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Platinum(II) to Some Biologicaly Important Thiols

Abstract: The reactions between [Pt(terpy)Cl+ and thiols, such as glutathione, L-cysteine, D-penicillamine and thioglycolic acid have been Studied by conventional UV-VIS spectrophotometry and H NMR spectroscopy. The second-ordero rate constants, K2, are similar for these four thiols, varying between 1.06 x 10-2 and 6.10 x 10+3 M-1 s-1 at 25°C. The activation entropies have large negative values between -100 and -200 J mol-1 which are compatible with an associative A mechanism. However, L-methionine, as thioether li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…The steric strain on [Pt(terpy)X] (2− n )+ type complexes is also another reason for the high reactivity 17. Therefore, a vast number of studies have been done on the kinetics of substitution of [Pt(terpy)X] n + ‐type complexes with various nucleophiles 8,13,14,17–33. In terms of their biological properties, these Pt(II) terpy complexes themselves have also been shown to bind to double‐stranded DNA through intercalation 34 and have been found to be cytotoxic against Trypanosoma and Leishmania parasites in addition to human ovarian carcinoma 35,36.…”
Section: Introductionmentioning
confidence: 99%
“…The steric strain on [Pt(terpy)X] (2− n )+ type complexes is also another reason for the high reactivity 17. Therefore, a vast number of studies have been done on the kinetics of substitution of [Pt(terpy)X] n + ‐type complexes with various nucleophiles 8,13,14,17–33. In terms of their biological properties, these Pt(II) terpy complexes themselves have also been shown to bind to double‐stranded DNA through intercalation 34 and have been found to be cytotoxic against Trypanosoma and Leishmania parasites in addition to human ovarian carcinoma 35,36.…”
Section: Introductionmentioning
confidence: 99%
“…Speci city and imperturbability. The real optical and biochemical effectiveness of our functionalization method has been tested by comparing the TDP-43 detection results with the standard approach based on the self-assembly monolayer of thiols, commonly used for metallic surfaces, including platinum 60,61 . In the thiols-based functionalization experiment (see methods for details), the detected ZDP redshift for an analyte concentration of 1pM was 5nm ( gure S6), ve-times lower than the value obtained with the core-shell architecture (27nm, Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…(Bailey et al, 1995) Although the high reactivity of the complex depend on the electronic interactions between the terpyridine system and Pt(II), (Hofmann et al, 2003) bulkiness of the terpy ligand has great influence on the characteristics of this complex. The substitution reactions of the [Pt(terpy)Cl] + complexes with different thioethers has been confirmed that there is no reaction, (Petrović B. et al, 1999;Bugarčić et al, 1997) which can be attributed to the strong steric effect. Although, the reactions of [Pt(terpy)Cl] + complexes with some S-methyl-thioethers and thiones may occur, but in this case as the product of reactions appear dinuclear platinum complexes in which the bridge ligand is S-methyl-group.…”
Section: Interaction Of [Pt(terpy)cl] + Complex With Sulphur-and Nitrmentioning
confidence: 90%
“…(Annibale et al, 1999) High reactivity of the [Pt(terpy)Cl] + complex in substitution reactions with thiols is explained by formation of intramolecular hydrogen bonds between protons from the thiol-group and outgoing chloro ligand, which further stabilizes the transition state. (Annibale et al, 1998;Petrović B. et al, 1999;Bugarčić et al, 1997) In the reaction between biologically relevant ligands and Pt(II) complexes, DNA fragments usually coordinated through the N7 atom to Pt(II). (Bugarčić et al, 2004b) Several products of the reaction between [Pt(terpy)Cl] + complex and DNA fragments were synthesized and characterized by X-ray analysis, in which the presence of strong intramolecular hydrogen bonds are observed.…”
Section: Interaction Of [Pt(terpy)cl] + Complex With Sulphur-and Nitrmentioning
confidence: 99%